HAWKWEED (PICRIS L.) AS A PERSPECTIVE SOURCE OF BIOLOGICALLY ACTIVE SUBSTANCES - V. N. Bubenchikova; I. V. Stepnova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The plants of the Hawkweed genus (Picris L.) belong to the Astrologic (Complex) family - Asteraceae (Compositae) and are used in folk medicine as diuretic, choleretic, laxative, analgesic, sudorific, emollient remedies. However, their chemical composition has not been studied sufficiently. Among other factors, in the process of the study sesquiterpene lactones were found in the aerial, including inflorescences, and subterranean parts; β-sitosterol was found in the leaves, and triterpenoids were found in the subterranean part of the plant. The aim of this work was the study of the qualitative composition and quantitative contents of biologically active substances of the Hawkweed herb. Materials and methods. As a material for the study, the aerial part of Hawkweed (Picris L.) was chosen. It was harvested in the vicinity of the city of Kursk in August 2016 and dried by air-shadow method. For the qualitative and quantitative analysis biologically active substances were extracted by various extractants (water, hydroalcoholic solutions, chloroform, hexane), and studied using conventional methods of phytochemical analysis. Results and discussion. The presence of carbohydrates (free and bound sugars, polysaccharides), organic acids, including ascorbic acid, phenolic compounds (tannins, flavonoids, coumarins, hydroxycinnamic acids), triterpene saponins, carotenoids has been established. The quantitative contents of water-soluble polysaccharides, pectin substances, organic acids, ascorbic acid, tannins, flavonoids, hydroxycinnamic acids, triterpene saponins, carotenoids have been determined. It was established that hydroxycinnamic acids, flavonoids, water-soluble polysaccharides, pectin substances represent the greatest significance of the investigated compounds of the Hawkweed herb. Conclusion. The carried out researches show that further phytochemical study of the Hawkweed herb is promising in order to study the possibility of its use in scientific medicine and the production of modern phytopreparations on its basis.